D-mannitol sensor based on molecularly imprinted polymer on electrode modified with reduced graphene oxide decorated with gold nanoparticles - Beluomini, Maísa Azevedo [UNESP]; da Silva, José L. [UNESP]; Sedenho, Graziela Cristina [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2017)
An electrochemical sensor for D-mannitol based on molecularly imprinted polymer on electrode modified with reduced graphene oxide decorated with gold nanoparticles was developed in this present work. The sensor was constructed for the first time via the electropolymerization of o-phenylenediamine (o-PD) over a surface containing reduced graphene oxide (RGO) and gold nanoparticles (AuNP) in the presence of D-mannitol molecules. The surface modification with AuNP/RGO-GCE facilitated the charge transfer processes of [Fe(CN)6]3−/4−, which was used as an electrochemical probe. It also contributed meaningfully towards the increase in the surface/volume ratio, creating more locations for imprinting, and providing greater sensitivity to the sensor. The MIP/AuNP/RGO-GCE sensor was characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), scanning electron microscope (SEM), atomic force microscope (AFM) and X-ray Photoelectron Spectroscopy (XPS). Important parameters that exert control over the performance of the molecularly imprinted sensor (such as number of cycles, pH, monomer and template concentration and extraction and rebinding conditions) were investigated and optimized. The imprinting factor was 4.9, showing greater response to the D-mannitol molecule compared to the interfering molecules. The limit of detection, limit of quantification and amperometric sensitivity were 7.7×10–13 mol L−1, 2.6×10–12 mol L−1 and 3.9×1010 µA L mol−1 (n=3) respectively. The MIP/AuNP/RGO-GCE sensor was successfully applied towards the selective determination of D-mannitol in sugarcane vinasse, thus making it, in essence, a valuable tool for the accurate and reliable determination of this molecule.
Keywords: Au nanoparticles; D-mannitol; Electrochemical determination; Molecularly imprinted electrochemical sensor; Reduced graphene oxide